World Conference on Fraternalism, Freemasonry & History: Research in Ritual, Secrecy and Civil Society (Bibliothèque Nationale de France, París, 2017) - Martínez García, Julio (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2018)
Reseña de la World Conference on Fraternalism, Freemasonry & History: Research in Ritual, Secrecy and Civil Society (Bibliothèque Nationale de France, París, 2017).